Adenoid hypertrophy in children with allergic disease and influential factors - Evcimik, Muhammed Fatih; Do?ru, Mahmut; Cirik, Ahmet Adnan; İşeri Nepesov, Merve (Elsevier Ireland, 2015)
Objectives: Adenoid hypertrophy (AH) may cause several comorbid conditions including sleep apnea, chronic serous otitis and sinusitis. Such conditions are more common among children with allergic diseases. In our study, we aimed to determine the patient profile associated with higher incidence of adenoid hypertrophy and the related influential factors. Methods: The study included 1322 children being treated and followed up for allergic conditions. 100 children with no allergic diseases presenting during the same period to the clinic were included as the control group. Skin prick test for the same allergens was performed for all patients. Adenoid tissue was analyzed by an ENT specialist and the diagnosis was confirmed based on the patient history, endoscopic physical examination and radiology. Results: Of the patients, 765 (57.9%) were males and 557 (42.1%) were females and their mean age was 5.9 ± 3.3 years. In the control group, 56 (56%) children were males and 44 (44%) were females and their mean age was 6.3 ± 4.1 years. Children with allergic disease and control subjects did not differ significantly by age and gender. Adenoid hypertrophy was identified in 164 (12.4%) of the patients with allergic disease and in 3 (3%) of the controls. Allergic children were divided into two groups, as children with and without AH, respectively. The groups did not differ statistically significantly by gender, age or familial history of atopic disease. However, cigarette smoke exposure at home and presence of allergic rhinitis was significantly more frequent in the group of patients with AH. In the logistic model investigating the effect of variables on AH presence (according to age, gender, cigarette smoke exposure, asthma, AR, AD presence, atopy presence, sensitivity to house dust, pollen, epithelium, Alternaria alternata and cockroach), AR presence and cigarette smoke exposure were statistically significant. Conlusions: AH frequency is higher in children with allergic disease compared to controls. The most common sensitivity to allergens among patients with AH was to house dust. Presence of allergic rhinitis and cigarette smoke exposure are risk factors for developing AH. Children with these risk factors should be questioned for AH during their routine examinations.
Keywords: Adenoid Hypertrophy; Adenoids; Allergic Disease; Allergic Rhinitis; Cigarette Smoking; Pediatric Diseases